2022
DOI: 10.1073/pnas.2107662119
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and infrastructure interact to drive tourism to and within Costa Rica

Abstract: Significance Tourism accounts for roughly 10% of global gross domestic product, with nature-based tourism its fastest-growing sector in the past 10 years. Nature-based tourism can theoretically contribute to local and sustainable development by creating attractive livelihoods that support biodiversity conservation, but whether tourists prefer to visit more biodiverse destinations is poorly understood. We examine this question in Costa Rica and find that more biodiverse places tend indeed to attract m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…The potential economic and conservation benefits of bird-watching have also been highlighted in regions prioritized for economic development such as post-conflict territories (Ocampo-Peñuela and Winton, 2017) which covered 50% of Forest Areas. Support for bird-watching tourism including infrastructure investment, training of local guides, and promoting those regions as world-class birding destinations is needed to meet goals for economic growth while protecting forest (Ocampo-Peñuela and Winton, 2017, Echeverry et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The potential economic and conservation benefits of bird-watching have also been highlighted in regions prioritized for economic development such as post-conflict territories (Ocampo-Peñuela and Winton, 2017) which covered 50% of Forest Areas. Support for bird-watching tourism including infrastructure investment, training of local guides, and promoting those regions as world-class birding destinations is needed to meet goals for economic growth while protecting forest (Ocampo-Peñuela and Winton, 2017, Echeverry et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental issues are also very important to evaluate sustainability. Several authors [2,9,11,27,49] refer that the development of sustainable tourism should be based on the suitable usage of natural resources and the cautious improvement of natural processes of the sites. In terms of DT routes, several authors mention the importance of the environmental issues, that need to be balanced in order to protect natural resources and assure that new investments can provide both biodiversity conservation and positive economic impacts for the local community.…”
Section: Environmental Sustainabilitymentioning
confidence: 99%
“…There is a need to balance tourism with the protection of the natural resources. Yet the degree to which biodiversity goals drive tourism, especially with respect to infrastructure is poorly understood, while investments in infrastructure must keep up with successful biodiversity conservation for tourism to create attractive economic revenue [49].…”
Section: Environmental Sustainabilitymentioning
confidence: 99%
“…Worku (2021) looked to assess the role of forest biodiversity conservation for tourism development in Tara Gedam monastery in Ethiopia, and the results demonstrated that 'biodiversity contributes to sustainable tourism development on the grounds that it has less impact on the environment than other industries, based on an enjoyment of the natural and cultural environment. ' Echeverri et al (2022) acknowledged that nature-based tourism has the potential to sustain biodiversity and economic development, yet the degree to which biodiversity drives tourism patterns, especially relative to infrastructure, is poorly understood. In an attempt to explore this relationship, the authors looked to examine the relationships between different types of biodiversity and different types of tourism and infrastructure in Costa Rica, and their results revealed more biodiverse places tend to attract more tourists, especially where there is infrastructure that makes these places more accessible.…”
Section: Project and Policy Reports And Academic Literature Reviewmentioning
confidence: 99%